Adjustable smoke ceramic mabkhara using local clay for traditional fragrance application - Nordin, Adam Iman; Abdul Wahab, Mohd Saleh; Mohd Khairi, Ahmad Afiq Irham; Shamsul Anuar, Muhammad Aidid; Mohd Faiz, Muhammad Azfar Haziq (2025)
This project introduces an innovative reinterpretation of the traditional mabkhara (incense burner) using local clay ceramic material combined with an adjustable smoke release system. Unlike conventional mabkharas that emit fragrance without control, this new design allows users to manually regulate the intensity and direction of the smoke through a rotatable or sliding vent system. The integration of natural, heat-resistant clay with a user-controlled ventilation system offers a safer, eco-friendly, and culturally rich alternative. The design is modular and aesthetically inspired by traditional Islamic and Malay forms while accommodating modern lifestyle needs. The product is suitable for various spaces including homes, prayer rooms, spas, and boutique commercial environments.